Macrophage-Derived Small Extracellular Vesicles in Multiple Diseases: Biogenesis, Function, and Therapeutic Applications - Ye, Jingyao; Liu, Xuehong (Frontiers in Cell and Developmental Biology, 2022)
Macrophages (Mφs), as immune cells, play a pivotal role against pathogens and many diseases, such as cancer, inflammation, cardiovascular diseases, orthopedic diseases, and metabolic disorders. In recent years, an increasing number of studies have shown that small extracellular vesicles (sEVs) derived from Mφs (M-sEVs) play important roles in these diseases, suggesting that Mφs carry out their physiological functions through sEVs. This paper reviews the mechanisms underlying M-sEVs production via different forms of polarization and their biological functions in multiple diseases. In addition, the prospects of M-sEVs in disease diagnosis and treatment are described.